The Model of Measuring the Process and Operating Effectiveness in Enterprises - Radosław Ryńca (Contemporary Economics, 2009)
Process management means, that the employees are not responsible for realization of particular functions, but for achieving the specified results of this actions. In the literature, you can find the examples of using the process approach at companies. Many firms have already identified the processes and are trying to manage them. That’s why, it is necessary to use the tool, which can enable the measurement and assessment of these processes. In the article, the author show the proposal of measurement the process and operating effectiveness.